BODY POLITICS - MCGANN, PJ (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This seminar explores the politics of defining deviance, how individuals "become" deviant, and the operation of social control in everyday life with special reference to the body. The body is an important carrier of individualized and social meanings. It is also a site of cultural struggle over these meanings. Some bodies, some ways of being in the body, and some uses of our bodies are considered deviant. Our bodies are regulated by many norms, both informally through stigma and formally through medical diagnoses and laws. But who creates these norms? How? And with what effects? How do people resist? This course seeks to unravel these relations by considering social control in everyday life through gendered appearance, demeanor, leisure, and occupational norms. Topics include clothing, body size, "disordered" eating, gender, sexuality, race, disabilities, and transgenderism. (NOTE: this course is an accepted Gender Studies Program course.)